Pengaruh Pendidikan Kewirausahaan terhadap Minat Berwirausaha Siswa Kelas XI SMK Dastamaco Bekasi - Maryono, Maryono; Dermawan, Dermawan (Neolectura, 2023)
Purpose of this study was to investigate the effect of teaching entrepreneurship on entrepreneurial interest among class XI students at SMK Dastamaco Bekasi. The research method used is associative quantitative method, the instrument obtained is an attitude scale with the Likert model. The research technique here adopts saturated random sampling based on a sample of 27 class XI students of SMK Dastamaco Bekasi for the academic year 2023-2024. Based on the simple linear regression test with Anova table, the Fcount value was 6.120 with a significance level of 0.021 <0.05, so the significance regression technique means that there is an influence of the entrepreneurship education variable (X) on the interest variable entrepreneurship (Y). Based on the results of calculating the determinant coefficient in the summary table model, the magnitude of R Square is 0.197. It can be concluded that the magnitude of students' interest in entrepreneurship (Y) caused by entrepreneurship education (X) is 19.70% while the remaining 80.30% is not affected by variables other. Based on the analysis, the t test was carried out by comparing tcount with ttable at a significant level (?) = 5% or 0.05 and (df) = 27-2 = 25. hypothesis accepted. And when comparing the significance value of 0.021 <0.05, the hypothesis is accepted which states that there is an influence between entrepreneurship education as the independent variable X on students' interest in entrepreneurship as the dependent variable Y in class XI SMK Dastamaco Bekasi.